(untitled) (Papeles, 2021)
Introduction: YouTube is a huge catalog of videos on various topics, and it is a precept to come to this social network to see tutorials and answer questions regarding a specific topic. The eduyoutubers facilitate the work as educational edutubers, but to be precise and rigorous in the selection of these, it is necessary to have resources and tools that allow us to evaluate them, under pedagogical criteria. This study presents as the main objective of the research, it defines a selection process that will determine a catalog of pedagogical and didactic videos of mathematics, for the secondary educational level in Italy, and in relation to those videos most used by the students. Methodology: A total of 4845 students, between the ages of 13 and 22 living in Italy, were asked which edutuber and/or YouTube channels they use to support mathematical learning, then five videos were analyzed and the aspects to be evaluated were identified in relation to the following criteria: curricular; technical, aesthetic and expressive; pedagogical; didactic mathematics; and accessibility. As an instrument for data and information collection, a questionnaire was acquired that was validated through expert judgment, Cronbach’s Alpha. Results and discussion: The results mainly show that the students use the YouTube social network, as the main resource for consultation and help, to understand mathematics at secondary educational levels, noting that there is no specific profile for the use of this social network. Conclusions: it is concluded that the clarity of the content presented is important for the students, but it is important above all how it is presented, when distinguishing the two channels that, given the parity of well-presented content, attend to and take care of the technical, aesthetic and expressive aspects.